Aspirations in rural Pakistan: An empirical analysis - Kosec, Katrina; Hameed, Madeeha; Hausladen, Stephanie (International Food Policy Research Institute, 2012)
To examine aspirations in rural Pakistan, we carried out an aspirations module with almost 5,000 individuals as part of a comprehensive household survey. Using respondents’ answers to questions about their aspirations in four dimensions (income, wealth, education, and social status), we constructed an index similar to those used by Beaman et al. (2012) and Bernard and Seyoum Taffesse (2012) to measure aspirations levels. Specifically, respondents were asked to report the level of personal income they would like to achieve, the level (value) of assets they would like to achieve, the level of education they would like a child of their same gender to achieve (re-coded as desired years of education), and the level of social status they would like to achieve (on a 10-step ladder of possibilities). An individual’s index score is increasing in their desired levels of achievement in these four dimensions